Do nauki, do zabawy, ten przeczyta, kto ciekawy - Niewiarowski, Wojciech; Galach, Wieslaw (Warszawa : Wydawn. Naukowo-Techniczne, 1991)
Stories, games and general information in the Polish language for pre-school children.
Keywords: Children's stories, Polish; Games -- Juvenile literature